Konflik Sosial Dalam Naskah Drama Berjudul Petang Di Taman Karya Iwan Simatupang Dan Satu Bangku Dua Laki-Laki Karya Triyono Kajian Intertekstual Dan Implementasinya Sebagai Bahan Ajar Sastra Di SMA - Desti Irmawati, Frisilia (2016)
The purpose of this study is, (1) describe the structure of the build script Afternoon in the Park works Iwan Simatupang and The Bench Two Men Triyono work; (2) describe social conflicts contained in the manuscript Afternoon in the Park works Iwan Simatupang and The Bench Two Men Triyono work; (3) describe the intertextual relationship in terms of social conflicts contained in the manuscript Afternoon in the Park works Iwan Simatupang and The Bench Two Men Triyono work; and (4) describe the implementation of the results of the analysis of social conflict of the drama script Afternoon in the Park Iwan Simatupang work with One Bench Two Men Triyono works using textual studies as teaching materials in high school literature. This research is qualitative descriptive case study research strategy rooted (embaded and case study). The object of this study is the social conflicts of the manuscript Afternoon in the Park works Iwan Simatupang and The Bench Two Men Triyono work with intertextual study. The data used in this study was the sentence and discourse in the afternoon in the park plays works of Iwan Simatupang and The Bench Two men work Triyono.Teknik data collection using techniques literature, see, and record. The data analysis technique used is the analysis model flow (flow models of analysis), which includes three main components, namely data reduction, data presentation, and drawing conclusions. Results of this study were (1) the structure of the drama contained in the manuscript Afternoon in the Park and The Bench Two men have aspects that are interrelated and reinforce each other, these structures include the theme and mandate, characterization, plot, setting / background; (2) social conflicts that can be analyzed in both these texts, namely personal and interpersonal conflicts, conflicts of interest, conflicts of realistic and non-realistic, constructive and destructive conflict, conflict areas of life (economy, business, politics, religion, and family); (3) social conflict intertextual relationship both these texts are personal, interpersonal, importance / interest, destructive, constructive, and family; (4) the results of this study can also be implemented into the teaching of literature in high school, especially class XII.